Tocilizumab in the treatment of critical COVID-19 pneumonia: A retrospective cohort study of mechanically ventilated patients. (February 2021) - Fisher, Matthew J.; Marcos Raymundo, Luis A.; Monteforte, Melinda; Taub, Erin M.; Go, Roderick
Highlights: Tocilizumab was not associated with significantly reduced mortality in mechanically ventilated patients with COVID-19 pneumonia. Patients who received tocilizumab were younger, presented with higher fever on the day of intubation, and had significantly fewer comorbidities than controls. Elevated interleukin-6 was associated with greater mortality risk; interleukin-6 levels were similar in the treatment and control group. Abstract: Objectives: The purpose of this study is to evaluate clinical outcomes in patients with critical COVID-19 pneumonia requiring invasive mechanical ventilation who were treated with tocilizumab Design: Single-center retrospective cohort study Setting: Stony Brook University Hospital, a 600-bed academic tertiary medical center in Suffolk County, New York Participants: Consecutive patients with COVID-19 confirmed by nasopharyngeal polymerase chain reaction (PCR) who were admitted to Stony Brook University Hospital between March 10 and April 2 2020 and required mechanical ventilation in any intensive care unit during their hospitalization Exposure: Treatment with tocilizumab while intubated Main Outcome: Overall mortality 30 days from the date of intubation Results: Forty-five patients received tocilizumab compared to seventy controls. Baseline demographic characteristics, inflammatory markers, treatment with corticosteroids, and sequential organ failure assessment (SOFA) scores were similar between the two cohorts. Patients who received tocilizumab had significantly lower Charlson co-morbidity index (2.0 vs 3.0, P = 0.01) than controls. There was a trend towards younger mean age in the tocilizumab exposed group (56.2 vs 60.6; P = 0.09). In logistic regression analysis there was no reduction in mortality associated with receipt of tocilizumab (odds ratio (OR) 1.04; 95% CI, 0.27–3.75). There was no observed increased risk of secondary infection in patients given tocilizumab (28.9 vs 25.7; OR 1.17; 95% CI, 0.51–2.71). Conclusion: When controlling for age, severity of illness, and co-morbidities, tocilizumab was not associated with reduction in mortality in this retrospective cohort study of mechanically ventilated patients with COVID-19 pneumonia. Further studies are needed to determine the role of tocilizumab in the treatment of COVID-19.